2014
DOI: 10.1038/ncomms4234
|View full text |Cite
|
Sign up to set email alerts
|

Photoautotrophic hydrogen production by eukaryotic microalgae under aerobic conditions

Abstract: Eukaryotic algae and cyanobacteria produce hydrogen under anaerobic and limited aerobic conditions. Here we show that novel microalgal strains (Chlorella vulgaris YSL01 and YSL16) upregulate the expression of the hydrogenase gene (HYDA) and simultaneously produce hydrogen through photosynthesis, using CO 2 as the sole source of carbon under aerobic conditions with continuous illumination. We employ dissolved oxygen regimes that represent natural aquatic conditions for microalgae. The experimental expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(37 citation statements)
references
References 27 publications
1
35
0
Order By: Relevance
“…Phylogenetic analyses indicate that the H-cluster domain of algal [FeFe]-hydrogenase is not likely to be ancestral, rather it is likely that the ancestral enzyme had a single ferredoxin binding domain at the N-terminus which was lost when these genes were laterally transferred to algae [32]. The simple algal enzyme containing only the Hcluster is thought to function during the fermentation of carbohydrate reserves [45,46] although photosynthetic H 2 production was recently demonstrated under fully aerobic conditions in the alga Chlorella vulgaris [47].…”
Section: Phylogenetic and Functional Diversity Of [Fefe]-hydrogenasesmentioning
confidence: 99%
“…Phylogenetic analyses indicate that the H-cluster domain of algal [FeFe]-hydrogenase is not likely to be ancestral, rather it is likely that the ancestral enzyme had a single ferredoxin binding domain at the N-terminus which was lost when these genes were laterally transferred to algae [32]. The simple algal enzyme containing only the Hcluster is thought to function during the fermentation of carbohydrate reserves [45,46] although photosynthetic H 2 production was recently demonstrated under fully aerobic conditions in the alga Chlorella vulgaris [47].…”
Section: Phylogenetic and Functional Diversity Of [Fefe]-hydrogenasesmentioning
confidence: 99%
“…Photosynthetic microorganisms have the genetic, metabolic, and enzymatic characteristics to produce hydrogen under anaerobic and limited aerobic conditions (Hwang et al 2014). The unicellular green algal species C. reinhardtii is one of the well-known hydrogen-producing algae Melis and Happe 2001;Girbal et al 2005).…”
Section: Biohydrogenmentioning
confidence: 99%
“…In further support of this, recent reports have suggested that [FeFe]-hydrogenase is capable of aerobic activity in strains of Chlorella. It was shown that Chlorella vulgaris could maintain hydrogen production under atmospheres of 21% (Hwang et al, 2014) or 15% (Chader et al, 2009) oxygen. The active pool of hydrogenase was estimated at ;30 units per mg of dry weight (Hwang et al, 2014).…”
mentioning
confidence: 99%
“…It was shown that Chlorella vulgaris could maintain hydrogen production under atmospheres of 21% (Hwang et al, 2014) or 15% (Chader et al, 2009) oxygen. The active pool of hydrogenase was estimated at ;30 units per mg of dry weight (Hwang et al, 2014). Last, in a recent paper by Godaux et al , the authors claim that in a transition from dark anoxia to light, high rate of hydrogen production decreased to lower rate, before the onset of oxygen accumulation.…”
mentioning
confidence: 99%